2021
DOI: 10.1590/0102-33062020abb0058
|View full text |Cite
|
Sign up to set email alerts
|

Is distyly in subtropical Psychotria brachyceras (Rubiaceae) similar to the general trends observed for the genus?

Abstract: Distyly is a floral polymorphism that promotes cross-pollination through precise pollination. Psychotria is a mostly tropical genus of distylous Rubiaceae. Although widely studied in Brazil, some regions/species are still poorly explored, which hinders the understanding of distyly system along a greater geographical range. Here, we studied a subtropical population of Psychotria brachyceras in southern Brazil. For this, we characterized morphs occurrence, reciprocity of sexual structures, mating and incompatibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Studies have shown that the deposition of incompatible pollen onto stigmas can reduce seed set in some distylous plants (Shore & Barrett 1984;Nicholls 1987;Keller et al 2014), and is referred to as pollen discounting (Harder & Wilson 1998). Longer S-styled stigmas may reduce the likelihood of selfpollen interference, potentially increasing the chances of compatible pollen deposition and successful seed development after intermorph pollination (Ree 1997;Trevizan et al 2021a). We showed that S-styled stigmas received more pollen grains than L-styled stigmas, which can be attributed to their longer length and may compensate for their position inside the corolla and the interference from self-pollen deposition, as suggested in the literature (Ree 1997;Trevizan et al 2021a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that the deposition of incompatible pollen onto stigmas can reduce seed set in some distylous plants (Shore & Barrett 1984;Nicholls 1987;Keller et al 2014), and is referred to as pollen discounting (Harder & Wilson 1998). Longer S-styled stigmas may reduce the likelihood of selfpollen interference, potentially increasing the chances of compatible pollen deposition and successful seed development after intermorph pollination (Ree 1997;Trevizan et al 2021a). We showed that S-styled stigmas received more pollen grains than L-styled stigmas, which can be attributed to their longer length and may compensate for their position inside the corolla and the interference from self-pollen deposition, as suggested in the literature (Ree 1997;Trevizan et al 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…Longer S‐styled stigmas may reduce the likelihood of self‐pollen interference, potentially increasing the chances of compatible pollen deposition and successful seed development after intermorph pollination (Ree 1997; Trevizan et al . 2021a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…About 1400 shrubby species that grow in tropical areas around the world belong to the Psychotria genus [ 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. In particular, Psychotria viridis ( Figure 7 A) is a member of the rubiaceae family that grows spontaneously in the humid areas of Central and South America [ 116 ].…”
Section: Psychotria Viridismentioning
confidence: 99%